2020
DOI: 10.1136/thoraxjnl-2020-215577
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings in fatal COVID-19 severe acute respiratory syndrome: preliminary experience from a series of 10 Spanish patients

Abstract: In December 2019, an outbreak of severe acute respiratory syndrome associated to SARS-CoV2 was reported in Wuhan, China. To date, little is known on histopathological findings in patients infected with the new SARS-CoV2. Lung histopathology shows features of acute and organising diffuse alveolar damage. Subtle cellular inflammatory infiltrate has been found in line with the cytokine storm theory. Medium-size vessel thrombi were frequent, but capillary thrombi were not present. Despite the elevation of biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…It is noteworthy that the prothrombotic state is clinically relevant even in patients who had received prior thromboprophylaxis [ 2 ]. In fact, microvascular endothelial injury, combined with cytokine overproduction, have been hypothesized as the key factor leading patients with severe COVID-19 to multiple organ failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the prothrombotic state is clinically relevant even in patients who had received prior thromboprophylaxis [ 2 ]. In fact, microvascular endothelial injury, combined with cytokine overproduction, have been hypothesized as the key factor leading patients with severe COVID-19 to multiple organ failure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…No histopathological features of organized pneumonia were found in that study. The case series of Recald-Zamacona et al [ 163 ] confirmed these correlations.…”
Section: Imaging and Histopathological Correlationsmentioning
confidence: 77%
“…Few studies have correlated imaging findings in severe cases of COVID-19 pneumonia with histopathological findings [ 162 , 163 , 164 , 165 , 166 , 167 ]. This issue was investigated especially in case reports and case series mainly based on CT features described in ante-mortem or post-mortem examinations [ 163 , 164 , 165 , 166 ].…”
Section: Imaging and Histopathological Correlationsmentioning
confidence: 99%
See 2 more Smart Citations